City blood: A visionary infrastructure solution for household energy provision through water distribution networks - Karaca, Ferhat; Camci, Fatih; Raven, Paul Graham (Elsevier, 2013)
This paper aims to expand current thinking about the future of energy and water utility provision by presenting a radical idea: it proposes a combined delivery system for household energy and water utilities, which is inspired by an analogy with the human body. It envisions a multi-functional infrastructure for cities of the future, modelled on the human circulatory system. Red blood cells play a crucial role as energy carriers in biological energy distribution; they are suspended in the blood, and distributed around the body to fuel the living cells. So why not use an analogous system – an urban circulatory system, or “city blood” – to deliver energy and water simultaneously via one dedicated pipeline system? This paper focuses on analysing the scientific, technological and economic feasibilities and hurdles which would need to be overcome in order to achieve this idea. We present a rationale for the requirement of an improved household utility delivery infrastructure, and discuss the inspirational analogy; the technological components required to realise the vignette are also discussed. We identify the most significant advance requirement for the proposal to succeed: the utilisation of solid or liquid substrate materials, delivered through water pipelines; their benefits and risks are discussed.
Keywords: Water and energy distribution; Integrated utility infrastructures; Hydrogen carrier; Emerging technologies; Futures infrastructures